Structured Macroporous Silicon/Graphene Heterojunction for Efficient Photoconversion - Yu, Hongtao; Chen, Shuo; Fan, Xinfei; Quan, Xie; Zhao, Huimin; Li, Xinyong; Zhang, Yaobin (Angewandte Chemie International Edition, 2010)
New roles of graphene as a protective layer and transparent charge collector are demonstrated in a structured macroporous Si (MPSi)/graphene (Gr) heterojunction, which shows stable photocurrent (see picture) and a maximum photoconversion efficiency of 2.36 % in 0.05 M H2SO4 without adding a redox pair.